An efficient green diversity oriented synthesis of pyrimidinone and indole appended macrocyclic peptidomimetics. Issue 2 (10th January 2019) - Pathoor, Rajeena; Puthiyedath, Thasnim; Bahulayan, D.
Graphical abstract: Highlights: A concise three step protocol for medium ring sized macrocycles. Ring system consists of pyrimidinone or indole and 1, 2, 3-triazoles. Macrocycles showed blue emission with high quantum yiled and large Stokes. shift. Macrocycles showed excellent inhibitory property towards CDK2. Macrocycles showed excellent cytotoxicity against MCF-7 cell lines. Abstract: A concise protocol for the synthesis of pyrimidinone/indole functionalized hybrid peptide macrocycles with varying ring size is described. The precursors of the macrocycles were obtained from the post reaction modification of multicomponent reaction products and were cyclized via copper (I) catalyzed [3 + 2] azide-alkyne cycloaddition. The macrocycles showed excellent inhibitory property towards CDK2 protein which is responsible for a variety of cancers and were also showed excellent cytotoxicity against human breast cancer cell line MCF-7.